Factors Responsible for Non-compliance of Glaucoma Patients to Topical Medications in Our Setup - Nazli Gul, Omer Ilyas, Sanaullah Jan, Hina Khan, Yousaf Jamal Mahsood (Pakistan Journal of Ophthalmology, 2018)
Purpose: To identify the factors affecting the compliance of glaucoma patients to topical medical treatment in our setup. Study Design: Cross sectional study. Place and Duration of Study: This study was carried out at department of clinical ophthalmology, KIOMS, Hayatabad Medical Complex, Peshawar from 1st February 2016 till 31st July 2016. Material and Methods: Patients meeting our inclusion criteria were recruited in this study on consecutive non-probability sampling technique. All the patients were interviewed and the causes of non-compliance to topical medical therapy were recorded. Stratification of non-compliance was also analyzed with respect to age groups and gender. Sample size was calculated using open epi software with confidence level of 95% and power of 80. Results: Total of 179 subjects participated in this study that had been advised topical anti-glaucoma medication. Mean age of our subjects were 51.9 ± 13.2 years with most (49.2%) of patients in age group between 50.01 – 65.00 years. Non-compliance was observed in 76.5% of patients with high cost of the medicines being on top of the list (54%). Male gender and older age group were found statistically significant to be more non-compliant. Conclusion: High cost of topical anti-glaucoma medications is the leading cause of non-compliance in our setup. Keywords: Glaucoma, Non-compliance, Non-adherence.